2019
DOI: 10.1038/s41375-019-0469-x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring tumour burden and therapeutic response through analysis of circulating tumour DNA and extracellular RNA in multiple myeloma patients

Abstract: Monitoring tumour burden and therapeutic response through analyses of circulating cell-free tumour DNA (ctDNA) and extracellular RNA (exRNA) in multiple myeloma (MM) patients were performed in a Phase Ib trial of 24 relapsed/refractory patients receiving oral azacitidine in combination with lenalidomide and dexamethasone. Mutational characterisation of paired BM and PL samples at study entry identified that patients with a higher number of mutations or a higher mutational fractional abundance in PL had signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 40 publications
5
55
0
5
Order By: Relevance
“…Patients with more than two mutations, or a fractional abundance of a mutation greater than 1%, had significantly shorter overall survival. These findings were validated by another study, where a higher absolute number of mutations, as well as a higher fractional abundance of these mutations, was also associated with worse overall survival [38] .…”
Section: Cfdna In MMsupporting
confidence: 53%
See 1 more Smart Citation
“…Patients with more than two mutations, or a fractional abundance of a mutation greater than 1%, had significantly shorter overall survival. These findings were validated by another study, where a higher absolute number of mutations, as well as a higher fractional abundance of these mutations, was also associated with worse overall survival [38] .…”
Section: Cfdna In MMsupporting
confidence: 53%
“…MM is the archetypal haematological disease for studying the utility of cfDNA and liquid biopsies. The marked spatial and temporal genetic heterogeneity of MM is well established, and the gold standard bone marrow biopsy is now recognised as not being genomically representative of the disease as a whole [36][37][38] . cfDNA, representing DNA from the tumour in its entirety, better captures the genetic diversity of MM compared with bone marrow (BM) samples alone [35][36][37][38] .…”
Section: Cfdna In MMmentioning
confidence: 99%
“…Subsequently, we used CRBN expression to adjust the levels of the 3 genes determined as per previous reports . Ratios of IKZF1 , IKZF3 , and KPNA2 to CRBN were calculated and analyzed for determining patient response to Ld therapy.…”
Section: Resultsmentioning
confidence: 99%
“…These exRNA biomarkers were identified and validated with credible clinical performance for non-invasive detection of gastric cancer. Another recent study reported analysis of ctDNA and exRNA for monitoring tumour burden and therapeutic response in patients with multiple myeloma [52] . This exploratory analysis has provided evidence of ctDNA for predicting disease outcome and the utility of exRNA as a biomarker of therapeutic response in multiple myeloma.…”
Section: Exrna As Cancer Biomarkermentioning
confidence: 99%